NEUROPSYCHOLOGICAL FUNCTIONS IN EPILEPSY PATIENTS - Masood, Sana; Rafique, Rafia (Journal of Ayub Medical College Abbottabad, 2012)
Background: Neuropsychological impairment can be associated with epilepsy and its different types. The present study investigated gender differences in neuropsychological functions in epileptic patients. It was hypothesized that neuropsychological functioning will be different in male as compared to female epileptic patients. It was also hypothesized that there are significant gender differences among male and female epileptic patients in depression, somatic complaints, memory, communication, aggression and motor impairment. In addition it was hypothesized that neuropsychological functioning among patients diagnosed with different types of epilepsy; grand mal, petit mal, complex partial and generalized tonic clonic will be different. Method: A sample of 60 patients was recruited from different hospitals situated in the city of Lahore through purposive sampling technique. To assess neuropsychological functions, Neurobehavioral Functioning Inventory (NFI) was used. NFI was translated and back translated through the process of validation and final version of the scale in Urdu was obtained for use in the study. ANOVA and Student's t-test were employed to infer the proposed hypotheses. Result: There is significant difference in neuropsychological functioning between male and female epileptic patients on only somatic complaints. Females were found to reveal greater somatic complaints compared to their male counterparts. There are significant differences in neuropsychological functioning among patients diagnosed with different types of epilepsy. Conclusions: The study lays ground for future research and holds implications for the implementation of gender based neuropsychological interventions. Keywords: Neurobehavioral functioning inventory (NFI), grandmal, petit mal, tonic clonic seizure